The essential structure of the challenges of caring for patients with pain : a phenomenological study - Katrín Blöndal (2004)
Verkefnið er opið nemendum og starfsfólki Háskólans á Akureyri Despite medical advances, hospitalised patients continue to suffer because of deficits in pain management, such as nurses’ under-medication. The aim of this study was to generate an in-depth understanding of what it is like for nurses to care for patients with pain. The purpose was to improve patients’ pain management. The research question was ‘what is the essential structure of nurses’ experience of caring for patients with pain?’ The research approach was phenomenology: the Vancouver School of doing phenomenology, and the sampling purposeful. The researcher participated in twenty dialogues (unstructured interviews), with the ten nurses who were co-researchers (participants), and were working on adult medical and surgical wards at three hospitals in Iceland. The data analysis was thematic, resulting in the essential structure of: ‘the challenges of caring for patients with pain’. Nurses’ experience of caring for patients with pain may be understood by viewing their role within a goal directed mission, where the nurses who have strong moral obligation to relieve pain, assumed the role of the patients’ advocates. Their mission was, however, complicated by several internal and external challenges and barriers. The most prevailing features were the fear of giving too much, strain of caring for addicts and terminal patients with pain, absence of or inadequate prescription, and sometimes lack of access to accountable physicians. A vital factor was to have decision on palliative care and clear rules about pain management, since such directives facilitated successful pain relief. One important turning point on the nurses’ journey was the ‘gate’ where they participated in mutual decisionv making along with the physician. Within these relations, having a voice was vital for the nurses while they generally felt that they were being listened to and respected. Knowing the patient and the physician facilitated all relations. Where physicians are responsible ...